FOOD TOURISM: THE ROLE OF LOCAL SPECIAL FOOD IN INCREASING AND DEVELOPING TOURISM IN INDONESIA - D. Iwan Riswandi (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine (1) the potential of local specialties as food tourism; and (2) local specialty food strategies as food tourism in increasing and developing tourism in Indonesia. This research uses SWOT analysis to analyze local specialty food strategies as food tourism in increasing and developing tourism in Indonesia. The results of this research show that (1) the diversity of typical foods that exist in each region is a potential that needs to be developed and is of concern to the government to manage it professionally which can increase the interest of tourists to come to visit Indonesia and generate foreign exchange in the tourism sector; and (2) the local specialty food strategy as food tourism in increasing and developing tourism in Indonesia consisting of the SO strategy through the promotion of food tourism by displaying local Indonesian specialties, the WO strategy by developing a food tourism concept to attract tourists, the ST strategy through collaboration with Tourism stakeholders support food tourism, and WT strategies through educating food tourism managers, especially tourism actors.